Microcystins production in Microcystis induced by Daphnia pulex (Cladocera) and Brachionus calyciflorus (Rotifera) - Alfredo Pérez-Morales (Hidrobiológica, 2015)
Freshwater cyanobacteria often are the predominant division of phytoplankton in eutrophic environments. Microcystis is a bloom-forming cyanobacterium, commonly found in urban lakes of central Mexico. Several biotic factors including the presence of zooplankton induce the production of toxins (microcystins, MCs) in Microcystis. Here, it present data on the effect of the presence of the cladoceran Daphnia pulex (Leydig, 1860) and the rotifer Brachionus calyciflorus (Pallas, 1776) on total MCs production in Microcystis spp. Results indicate that Microcystis spp. with or without the presence of zooplankton (controls), contained certain level of MCs (1.32 to 3.98 x 10-4 ng/cell). At low cell density of Microcystis spp. (0.5 x 106 cells/mL) and, in the presence of high zooplankton abundance (25 cladocerans or 250 rotifers, in 50 mL), the MCs concentration was significantly higher as compared to controls. Moreover, under low zooplankton density and at low density of Microcystis spp., the MCs levels did not vary significantly. Compared to rotifers, the presence of cladocerans resulted in higher MCs levels. This work demonstrates that zooplankton presence may induce microcystins production in Microcystis spp.